2020
DOI: 10.1177/1934578x20953276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Processing Parameters on Polyphenols, Flavonoids, and Antioxidant Activities of Codonopsis javanica Root Extract

Abstract: The root of a ginseng-like plant named Codonopsis javanica is a valuable ingredient in folk medicine with diverse biological properties and has been used in treatments for various diseases, including leukemia, inflammation, and hepatitis. This study aimed to optimize various parameters related to the extraction process of C. javanica root (CJR) with respect to total phenolic content (TPC), total flavonoid content, and antioxidant activities of the obtained CJR extract. We first performed a series of single-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The regression coefficient (R 2 ) of 0.9812 showed that 98.12% of the experimental data are compatible with the predicted data by the model. In particular, the predicted R 2 (0.9643) is very close to adjusted R 2 (0.9891), suggesting a better fit for the quadratic model [24,25].…”
Section: Suitability Of the Modelmentioning
confidence: 58%
“…The regression coefficient (R 2 ) of 0.9812 showed that 98.12% of the experimental data are compatible with the predicted data by the model. In particular, the predicted R 2 (0.9643) is very close to adjusted R 2 (0.9891), suggesting a better fit for the quadratic model [24,25].…”
Section: Suitability Of the Modelmentioning
confidence: 58%
“…This may be due to differences in raw material origin, collecting time, and extraction conditions. In general, the polyphenols content of the aqueous extract of "Cao Khai" was higher than that of other medicinal root-derived materials such as Angelica sinensis (32.79 μgGAE/mg), Condonopsis javanica (2.9 μgGAE/mg) (Ng et al, 2020;Pham et al, 2020). Current findings indicated that C. flavescens possessed significant amounts of polyphenols and flavonoids.…”
Section: Contents Of Total Polyphenols and Flavonoids Compoundsmentioning
confidence: 74%
“…The content of total phenolics is determined by Folin‐Ciocalteu colorimetric method (Dao et al., 2021; Pham et al., 2020). First, 1 g samples are extracted with distilled water and refer to nearest volume.…”
Section: Methodsmentioning
confidence: 99%